Effect of Dried Tomato Pomace Feeding on Feed Intake, Body Weight Gain and Economic Efficiency of Rhode Island Red Grower Chicks - Yitbarek, Melkamu Bezabih (International Journal of Natural Sciences, 2013)
This experiment was carried out to evaluate the effect of feeding Dried Tomato Pomace (DTP) with commercial ration on feed intake, body weight gain, feed conversion ratio (FCR) and economic efficiency of Rhode Island Red (RIR) grower chicks. A total of three hundred RIR grower chicks at the age of eight weeks were grouped into 20 pens of 15 chicks each, and randomly assigned to five treatments (control fed a commercial ration; 5% DTP;10% DTP; 15% DTP; 20% DTP). Birds fed on 5, 10, 15,and 20% DTP had the higher dry matter (DM) intake (72.93, 72.75, 72.98 and 73.15 g/bird/day) than the control group (72.10g/bird/day). The daily body weight gain of birds ranged from 13.3 to15.3 g/day, the highest being on birds fed on 5% DTP; The feed conversion ratio (FCR) of birds were 5.3, 4.8, 5.0, 5.3, and 5.5 for the control and for birds that consumed 5, 10, 15, and 20% DTP, respectively. The higher significant difference (p<0.05) was observed at 5%compaired with 20% DTP. The economic efficiency of the experimental diets was 1.35, 1.79, 1.80, 1.78, and 1.82 for a group fed on the control, 5, 10, 15, and 20% DTP, respectively. There was a higher significant (p<0.05) difference on a group fed on DTP and the control diet. 20% DTP brought the highest economic efficiency among the groups. Based on these results it could be concluded that dried tomato pomace could be incorporated at the level of 20% without any adverse effect on growth performance in order to increase the economic efficiency DOI: http://dx.doi.org/10.3329/ijns.v2i4.13286 International Journal of Natural Sciences (2012), 2(4) 99-103